2005
DOI: 10.1242/jcs.02381
|View full text |Cite
|
Sign up to set email alerts
|

PfEMP1 expression is reduced on the surface of knoblessPlasmodium falciparuminfected erythrocytes

Abstract: . (1995). Cloning the P. falciparum gene encoding PfEMP1, a malarial variant antigen and adherence receptor on the surface of parasitized human erythrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 49 publications
5
89
0
2
Order By: Relevance
“…However, a circular zone of clearing is also evident around the edges of the knob protrusions, similar to what was seen previously by low-resolution freeze-fracture SEM of the P-face ( Figure 7B). 19,39 These findings demonstrate that the knob membrane has a distinct distribution of membrane proteins from the surrounding erythrocyte membrane, including a discrete structure at the apex.…”
Section: Membrane Proteins Are Reorganized At Knobsmentioning
confidence: 94%
See 2 more Smart Citations
“…However, a circular zone of clearing is also evident around the edges of the knob protrusions, similar to what was seen previously by low-resolution freeze-fracture SEM of the P-face ( Figure 7B). 19,39 These findings demonstrate that the knob membrane has a distinct distribution of membrane proteins from the surrounding erythrocyte membrane, including a discrete structure at the apex.…”
Section: Membrane Proteins Are Reorganized At Knobsmentioning
confidence: 94%
“…[18][19][20] KAHRP is localized with PfEMP1 in knobs, 18,21 where it has been shown by immuno-EM to be associated with an electron-dense (as visualized in heavy metal-stained specimens) layer of material under the membrane, as well as in Maurer's clefts. 22,23 KAHRP is a 59-72 kDa protein (550-657 amino acid residues depending on the variant) containing an N-terminal signal sequence and a PEXEL (Plasmodium export element) motif that mediate export into the erythrocyte, a 63-amino acid histidine-rich (55%) region, and 2 variable tandem repeat regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Truncation of the kahrp gene, that encodes KAHRP, leads to development of knobless IEs. Knobless IEs are known to Onyambu et al 17 have reduced ability to bind to purified receptors compared to knobbed IEs (Horrocks et al, 2005). Recent published data has shown that clumping parasites can be selected from knobless parasite line DD2 (Arman et al, 2013).…”
Section: Mechanisms For Platelet-mediated Clumpingmentioning
confidence: 99%
“…This pfEMP-1 is a key virulent factor for Plasmodium falciparum infection. This protein is expressed on the surface of infected erythrocytes and directly mediates adhesion to a variety of host cells [12].…”
Section: Cellular Adaptationsmentioning
confidence: 99%